Revisiting Discharge Mechanism of CFx as a High Energy Density Cathode Material for Lithium Primary Battery. Issue 5 (29th December 2021) - Sayahpour, Baharak; Hirsh, Hayley; Bai, Shuang; Schorr, Noah B.; Lambert, Timothy N.; Mayer, Matthew; Bao, Wurigumula; Cheng, Diyi; Zhang, Minghao; Leung, Kevin; Harrison, Katharine L.; Li, Weikang; et al.
Abstract: Lithium/fluorinated graphite (Li/CFx ) primary batteries show great promise for applications in a wide range of energy storage systems due to their high energy density (>2100 Wh kg –1 ) and low self‐discharge rate (<0.5% per year at 25 °C). While the electrochemical performance of the CFx cathode is indeed promising, the discharge reaction mechanism is not thoroughly understood to date. In this article, a multiscale investigation of the CFx discharge mechanism is performed using a novel cathode structure to minimize the carbon and fluorine additives for precise cathode characterizations. Titration gas chromatography, X‐ray diffraction, Raman spectroscopy, X‐ray photoelectron spectroscopy, scanning electron microscopy, cross‐sectional focused ion beam, high‐resolution transmission electron microscopy, and scanning transmission electron microscopy with electron energy loss spectroscopy are utilized to investigate this system. Results show no metallic lithium deposition or intercalation during the discharge reaction. Crystalline lithium fluoride particles uniformly distributed with <10 nm sizes into the CFx layers, and carbon with lower sp 2 content similar to the hard‐carbon structure are the products during discharge. This work deepens the understanding of CFx as a high energy density cathode material and highlights the need for future investigations on primary battery materials to advance performance. Abstract : The discharge reaction mechanism of fluorinated graphite (CFx ) as a cathode material for lithium primary batteries is investigated using advanced characterizations, including different ex situ spectroscopic techniques and cryogenic electronic microscopy. The results show that lithium fluoride particles with <10 nm sizes within CFx layers and disordered carbon are the products during discharge. This work is expected to assist the future development of primary batteries using CFx .